PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN AKTIVITAS TERHADAP SUSTAINABILITY REPORT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2013-2015) - Lydia Noor Said, 13.05.52.0016; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyzethe effect of profitability, liquidity, leverage, and activity on sustainability report on manufacturing companies. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2013-2015. The sampling technique is purposive sampling. Based on purposive sampling obtained a sample of 61 companies. Data analysis technique used is multiple linear regression analysis. The results of this study show that each variable has a different effect, namely profitabilitas leave a positive and significant impact on sustainability report, liquidity positively influence and insignificant impact on sustainability report, leverage has a negative and significant impact on sustainability report, while aktivitas has a negative impact and no significant effect on sustainability report.Keywords: Profitability, Liquidity, Leverage, Activity, and Sustainability Report